Fundamental Properties of Ply Bamboo - Jajang Suryana; Muhammad Y Massijaya; Yusuf Sudo Hadi; Dede Hermawan (Jurnal Ilmu dan Teknologi Kayu Tropis, 2011)
Physical and mechanical properties of ply bamboo made from various bamboo species and adhesive type were studied. Bamboo species used in this study were tali (Gigantochoa apus), andong (Gigantochloa verticillata), and betung (Dendrocalamus asper). Five types of adhesives were used for the experiment, namely methylene diphenyl isocyanate (MDI), phenol formaldehyde (PF), melamine formaldehyde (MF), urea formaldehyde (UF), and poly vinyl acetate (PVAC). Three layer of ply bamboo with (40x40x0,4) cm3 in size was made by weight spread of adhesive 200 g m-2, compression temperature at 140 ºC for MDI and PF, 110 ºC for MF and UF, and room temperature for PVAc adhesives, with specific pressure of 15 kg cm-2 for five minutes. Especially for PVAc, cold compression was carried out using a clamp for 24 h. Fundamental properties of ply bamboo was tested according to SNI 01-5008.7-1999. The results showed that the development dimension of the ply bamboo from the largest to the smallest was in the side of thick, wide, and long, while for timber and plywood were in the side orientation of tangential (width), radial (thick), and longitudinal (long). The best physical and mechanical properties of ply bamboo were obtained from betung bamboo using MDI adhesive.Key words: melamine formaldehyde, methylene diphenyl isocyanate, phenol formaldehyde, ply bamboo, poly vinyl acetate